A sustentabilidade do Programa na Vila Rural São Camilo - Palotina - PR: um estudo de caso - Ventorim, Sandra Tercia Ferneda (2017)
The present study presents results of a research on a characterization of the residents and the practice of the Rural Village State Program, having as object the Vila Rural São Camilo, located in the municipality of Palotina, in the State of Paraná. The research identified the profile of the villager of Vila Rural and how the program is put into practice. We analyzed the factors that make it difficult to achieve the objectives of the program, such as the production goal for self-consumption. The research was done through the collection of primary and secondary data, having as an open and closed questions, applied to all 42 families residing in Rural Village, In the response to the invitation to participate, it is highlighted that the majority of families were represented by the female. The results showed that few carry out a commercialization of the products, as well as perform functions to meet their financial needs. It was also observed that the inhabitants of Vila Rural have a shortage of financial resources, and that they depend on programs provided by Government, and also, that there is a lack of technical incentive, for a population that does not plant the products and their commercialization.